Effects of Re on Vacancy Mobility in a Ni-Re System: An Atomistic Study - Nuttapong La-ongtup; Suttipong Wannapaiboon; Piyanut Pinyou; Worawat Wattanathana; Yuranan Hanlumyuang (Journal of Chemistry, 2021)
The performance of modern Ni-based superalloys depends critically on the kinetic transport of point defects around solutes such as rhenium. Here, we use atomistic calculations to study the diffusion of vacancy in the low-concentration limit, using the crystalline fcc-framework nickel as a model. On-the-fly kinetic Monte Carlo is combined with an efficient energy-valley search to find energies of saddle points, based on energetics from the embedded atom method. With this technique, we compute the local energy barriers to vacancy hopping, tracer diffusivities, and migration energies of the low-concentration limit of Ni-Re alloys. It was estimated that the computed diffusion rates are comparable to the reported rates. The presence of Re atoms affects the difference between the energy of the saddle point and the initial energy of point defect hopping. In pure Ni, this difference is about 1 eV, while at 9.66 mol% Re, the value is raised to about 1.5 eV. The vacancy migration energy of vacancy in the 9.66 mol % Re sample is raised above that of pure Ni. Our findings demonstrate that even in the low-concentration limit, Re solute atoms continue to play a crucial role in the mobility of the vacancies.